Pemberdayaan Kelompok Pekerja Bella Café dalam Penerapan Hygiene Perusahaan di Desa Jimbaran, Kuta, Badung - Tanjung Subrata; Ni Wayan Rusni; Dewa Ayu Putu Ratna Juwita; Asri Lestarini (Publikasi Indonesia, 2022)
Indonesia has been experiencing the COVID-19 pandemic for more than a year. This pandemic has paralyzed the tourism industry, especially in Bali. The recovery of this industry must of course be accompanied by awareness from the public and tourism actors about the needs of tourists regarding the guarantee of high cleanliness, health, safety and environmental sustainability of the service products provided to tourists. One of the tourism actors in Bali is the owner and worker of the Café in Jimbaran, Kuta, Badung. The café, which sells entirely fish and seafood-based dishes, must prepare itself for the recovery of the tourism industry. The low hygiene behavior and health protocols cause the need for training and assistance regarding company hygiene for the owners and workers of Bella Café in Jimbaran, Kuta, Badung who are members of the Café 19 Group. After the training, an evaluation of the training that has been provided will be carried out. The result of this activity is an increase in knowledge as seen from the average posttest (94.00) which is higher than the pretest average (62.00). After being observed, there was an increase in the behavior of Bella Café workers in following the company's health and hygiene protocols. It is hoped that similar activities can be carried out so as to refresh Bella Café workers in maintaining behavior in accordance with the health protocol to support the quality of service to guests during the COVID-19 pandemic.